Central Asian Transboundary Waters in the Age of Globalization: Problems of Legal Regulation and International Cooperation - BAIDELDYNOV, Daulet; JANGABULOVA, Araylym; YEREZHEPKYZY, Roza; BERDIBAУEVA, Aliya; KHAMIT, Aidos (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
In the current situation global water’s crisis, despite active measures of the world’s community in the direction of its resolution, gains the acuteness of situation year by year. In this context, the difficulties in determining the legal status of transboundary waters’ definition are escalated by the intensification of the global trend towards the activization of ecosystem’s stability. Practically, taking into account generous amount of problems in the sphere of transboundary water resources’ management Central Asia countries at this time aren't ready to the approbation of the specified approach and are only at the stage of normative consolidation of effective interstate cooperation in the explored sphere. Within the conducted research the polyvariety of the definition “transboundary waters” was analyzed; problems of legal regulation of transboundary waters’ usage in the Central Asian region were solved; water resources’ influence on of the Central Asian countries’ international cooperation was characterized. For further positive interstate cooperation integrated technical water interstate agreement which would become the fundamental basis on the way of Central Asian states’ stable water policy formation and would formalize the effective mechanism of water apportioning’ realization in practice was recommended to conclusion. It was argued that formation of the integrated newly-formed independent interstate association in the form of Visegrad Countries would become the most perspective blueprint of transboundary waters’ cooperation development.